Improving the students' academic English essay writing achievement through rubrics and peer correction - I Made Wardhana; Ni Luh Putu Sri Widhiastuty (English, 2018)
This study attempted to find out the contribution of rubrics and peer correction in improving the students’ achievement in academic English essay writing in terms of what the students’ perception on the application of rubrics and peer correction in academic English essay writing was; what the students’ academic English essay writing achievement was after being exposed through rubrics and peer correction; whether there was a correlation between rubrics and peer correction and the students’ academic English essay writing achievement. The data were collected from a distributed questionnaire consisting of a five-scale statement and open-ended questions to be responded by 60 samples of two classes out of 9 classes of semester 5 students of English Department of Faculty of Teacher Training and Education of Mahasaraswati University Denpasar in academic year 2016/2017 and the achievement of the students’ academic English essay from a determined thesis statement after being exposed to the application of rubrics and peer correction; both of whose scores were confronted to obtain the correlation. The result showed that there was a strong correlation (0.62) between the students’ perception on the application of rubrics and peer correction and their academic English writing achievement meaning that that rubrics and peer correction had a positive contribution in improving the students’ academic English writing achievement. Therefore, it was logical to recommend that rubrics and peer correction be applied as one of the techniques in improving academic English essay writing.